Rancang Bangun Mesin Pembungkus Kabel Menggunakan Motor Listrik 3 Fasa - Pratama, Febryan Rauf; Afandi, Slamet (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2024)
Occasionally, electricity serves as the primary source in our daily lives. Virtually all human activities rely on electricity. Cables are necessary to transmit electricity from one location to another. One of the stages in cable production is the sheeting process, which often results in visual defects. Stickiness in the cables is a common visual defect. Therefore, a machine is required to minimize these cable defects. The motor is a crucial component of such machines and is widely used in industrial processes involving rotating rotors or similar tasks. There are various types of motors available, including DC and AC motors. AC motors are commonly used for continuous spinning over long periods, while DC motors are preferred for maintaining a consistent and controlled speed. Based on our calculations, the motor current for motor 1 is 0.391 amperes, and for motor 2, it is 0.26 amperes. Additionally, the calculated motor torque is 1750 Nm.